"Elasto‐lung point": A new tool for the sonographic confirmation of pneumothorax. (4th May 2020) - Bandelli, Gian Piero; Levi, Guido; Quadri, Federico; Marchetti, Gian Pietro
Abstract: Introduction: Standard ultrasound gives the operator a dynamic morphology of the investigated anatomy, whereas ultrasound elastography (USE) provides quantitative and qualitative information about the elastic properties of the tissues. Objectives: We designed a single‐arm prospective study in order to investigate the feasibility of USE in the diagnosis of pneumothorax if a lung point sign is present. Methods: Thirty patients were enrolled in this protocol, from January 2017 to December 2018 at the Pneumology Department of the Azienda Socio‐Sanitaria Territoriale Spedali Civili (Brescia, Italy). Patients who were suspected of having pneumothorax were previously evaluated with standard ultrasonography, and then, in the presence of lung point, we performed strain elastography. All patients were evaluated in supine and sitting positions with a linear probe (7.5 MHz). USE enhanced the air‐tissue interface dividing the normal parenchyma from the air column of pneumothorax with a sharp line. We called this sign "elasto‐lung point." Results and conclusion: The "elasto‐lung point" was able to confirm the diagnosis of pneumothorax in every investigated patient. USE is a simple, reproducible and inexpensive technique that can contribute to the diagnosis of pneumothorax, such as the classic "stratosphere" or "Bar Code" sign in M‐mode. No false negative cases were observed.